First Aid and Prognosis for Acute Pneumonia - Klepikov, Igor (Global Journal of Medical and Clinical Case Reports, 2025)
Acute inflammation of the lung tissue, despite the constantly declared reports on the achievement of success in the treatment of these processes, remains one of the urgent problems of modern medicine, having turned in recent years into a subject of concern and unpredictability of the final results. The reason for this state in solving this problem is the inattention to a number of side effects of antibiotics, which still play the role of the main therapeutic agent for these diseases. The hope for a narrowly targeted antimicrobial action of these drugs leaves aside the classical canons of medical science. All the noted facts indicate the decisive role of didactic education under the influence of antibiotics in choosing adequate and effective solutions.